Economics of Bandwidth: Evolutionary-Economic and Cultural-Anthropological Reflections on Interfaces in Human-Machine-Complexes - Schwarz, Richard; Wäckerle, Manuel (Momentum Quarterly, 2012)
In this article we discuss bandwidth as a cognitive, cultural and technical rule, a rule limiting information transfer per unit of time. We understand the economy, culture and the society as an evolving rule-based system and assign bandwidth a central role, as a generic rule. Thereby we investigate theoretically the interactive processes of bandwidth exploitation and expansion in human-machine complexes. Furthermore we refer to the historical dimension of the digitalised society and discuss cultural developments of evolving prosthesis. In this context we derive a genealogy of equality and liberty in the net. Finally we look into two examples of evolving prosthesis, i. e. “automated trading” and the issue of “friendship capital in facebook”. It appears that systemic risk accumulates in similar kinds in both examples, though they seem rather diverse at a first glance. Our paper tries on the one hand to clarify crucial issues of the economics of bandwidth and on the other hand to develop some first interdisciplinary schemata of thought to tackle it scientifically.